Functional perturbation of classical natural killer and innate lymphoid cells in the oral mucosa during SIV infection - Li, Haiying; Reeves, R. Keith (Frontiers in Immunology, 2013)
Despite the fact that the majority of human pathogens are transmitted across mucosal surfaces, including the oral mucosae, oral immunity is poorly understood. Furthermore, because the normal flora of the oral cavity is vast and significantly diverse, host immunity must balance a complex system of tolerance and pathogen recognition. Due to the rapid recognition and response to pathogens, the innate immune system, including natural killer (NK) cells, likely plays a critical role in mediating this balance. Because logistical and ethical restraints limit access to significant quantities of human mucosal tissues, nonhuman primate models offer one of the best opportunities to study mucosal NK cells. In this study we have identified both classical NK cells, as well as innate lymphoid cells (ILCs) in tonsillar and buccal tissues and oral-draining lymph nodes. Identified by mutually exclusive expression of NKG2A and NKp44, NK cells and ILCs in the oral mucosa are generally phenotypically and functionally analogous to their gut counterparts. NKG2A+ NK cells were more cytotoxic while NKp44+ ILCs produced copious amounts of IL-17 and TNF-α. However, in contrast to gut, oral NK cells and ILCs both produced large quantities of IFN-γ and the beta-chemokine, MIP-1β. Also in contrast to what we have previously found in gut tissues of SIV-infected macaques, we found no reduction in NK cells during chronic SIV infection, but rather an expansion of ILCs in oral-draining lymph nodes and tonsils. These data suggest that the lentivirus-induced depletion of the NK cell/ILC compartment in the gut may be absent in the oral mucosa, but the inherent differences and SIV-induced alterations are likely to have significant impact on preventing oral opportunistic infections in lentiviral disease. Furthermore, these data extend our understanding of the oral innate immune system in general and could aid future studies evaluating the regulation of both normal oral flora and limiting transmission